Biopolymers for Liver Tissue Engineering: A Systematic Review - John Ong; Jacky Junzhe Zhao; Carla Swift; Athina E. Markaki (Gels)
Stem cell-derived liver cells, organoids, and lab-grown liver tissue are promising regenerative therapies for liver disease. However, current culture conditions are sub-optimal, producing end-target cells and tissue phenotypes that are immature or unstable when compared to primary liver cells and tissue. Biopolymers used in culture substrates and scaffolds for tissue engineering significantly impact the quality of the end-target cells and tissue, influencing the efficacy of regenerative treatments. In addition, the biochemical properties of some biopolymers may preclude the translation of downstream bioengineered products into clinical practice. Therefore, this systematic review aims to evaluate the recent advances in biopolymers within liver tissue engineering, providing an overview of the current usage in the field and highlighting novel substrates that have strong potential to be translated into clinical therapy.